Pengaruh Sistem Pembelajaran Daring, Motivasi Belajar Terhadap Prestasi Mahasiswa Dengan Minat Belajar Sebagai Variabel Moderasi - Nuri Annisa Fitri; Hisbullah Basri (UNIVED Press, 2022)
The purpose of this study was to determine the effect of the System Online Learning, Learning Motivation on Student Achievement, moderated by the variable Interest in Learning. Students of the Faculty of Economics, Tridinanti University, Palembang, became respondents in this study. There are two methods used in this study, namely simple regression analysis and moderated regression analysis. The first hypothesis is that the output value of the correlation Fcount is 58,591 with a Sig value. = 0.000 < significant criteria, namely 0.05. This shows that learning motivation has a positive and significant effect on student achievement. The results of the second hypothesis test using Moderated Regression Analysis, the value of R Square in the first regression is 0.272 or 27.2% and R Square in the second regression is 0.387 or 38.7% and the significance is 0.000, which means < significance 0.05 criteria. This shows that the learning motivation variable is able to moderating the effect of the online learning system on student achievement.